Re: Intra-operative Oxycodone Reduced Postoperative Catheter-Related Bladder Discomfort Undergoing Transurethral Resection Prostate. A Prospective, Double Blind Randomized Study - Doo, A Ram; Shin, Yu Seob; Kim, Myung Kim (Urology Journal, 2020)
none